The We Can Quit2 Smoking Cessation Trial: Knowledge Exchange and Dissemination Following a Community-Based Participatory Research Approach - Hayes, Catherine; Darker, Catherine (My University, 2022)
Background: 'We Can Quit2' pilot randomised controlled trial determined the feasibility [of conducting a community-based trial of We Can Quit, a peer-delivered stop-smoking programme (group support, combination nicotine replacement therapy (NRT), and tailored individual support) for women living in socioeconomically disadvantaged areas in Ireland. Lessons from a knowledge exchange (KE) workshop that reengaged trial stakeholders are presented. Methods: The trial dissemination plan included invitation of community, regional and national stakeholders (n = 176) to a KE interactive workshop, who received an accessible brief beforehand. Trial findings were presented. Enhancements to community engagement, participants' recruitment and retention, and policy priorities arising from the research were discussed. Field notes and responses to a post-event anonymous questionnaire were analysed using thematic content analysis. Results: Workshop attendees (41/176, 23%) recommended: dedicated additional time to engage community stakeholders; social prescribing pathways to enhance recruitment; more adaptation of trial-related information and assistance in completion of data forms for low literacy individuals; encouraging women to join healthy community programmes to facilitate retention and sustainability; removal of barriers to access NRT; and ongoing provision of cessation services tailored to disadvantaged groups. Conclusions: The findings are relevant to the implementation of other community-based health interventions for disadvantaged groups, to policy makers and to service providers.
PUBLISHED
Keywords: Women; Socioeconomic disadvantage; Smoking cessation; Pilot randomised controlled trial (RCT); Pilot cluster randomised trial (cRCT); Knowledge exchange and dissemination; Community-based participatory research (CBPR); Cancer; Inclusive Society; Community Health; Knowledge Exchange; SMOKING CESSATION PROGRAMS